Globalisasi Sosial Berpengaruh Negatif bagi Pertumbuhan Ekonomi di ASEAN?? - Heru Wahyudi; Qurrota Ayunindien (Penerbit Goodwood, 2022)
Purpose: The purpose of this study was to examine the impact of economic globalization, social globalization and politc globalization on economic growth in ASEAN. Research methodology: The analytical method used in this study is the Panel Data Analysis method for 6 countries in 2010 until 2017. The independent variables were economic globalization, social globalization and politic globalization and then support variables is infrastructure. Results: The results showed that there was a positive and significant relationship between economic globalization, politic globalizatioan and infrastructure on economic growth, while social globalization had a negative and significant effect on economic growth in ASEAN. Limitations: The limitation in this study is not counting all asean countries. Contribution:The results obtained from this study are expected to be one of the references in making policy directions based on the data presented to as a means for ASEAN countries to expand economic opportunities and increase economic growth.